The effects of solar radiation modification on solar and wind resource and power generation in the Caribbean - Matthew St. Michael Williams; Leonardo A. Clarke; Randy Koon Koon; Michael A. Taylor; Jayaka D. Campbell; Tannecia S. Stephenson (PLoS ONE, 2025)
The slow pace of global mitigation efforts has led to increased interest in Solar Radiation Modification (SRM) as a means for rapidly and artificially cooling the planet. Deploying SRM technologies, however, may directly alter renewable energy resources. This makes it a concern for Caribbean countries which are investing heavily in Variable Renewable Energy (VRE) to reduce their reliance on imported energy and meet climate change mitigation goals. In this study, solar irradiance output is extracted from the HadGEM2-ES global climate model run using the G4 (Stratospheric Aerosol Injection) SRM scenario from the Geoengineering Model Intercomparison Project (GeoMIP). The data is extracted for two future time periods corresponding to when global surface temperatures are projected to be 1.5 ∘C and 2.0 ∘C  above pre-industrial levels using the HadGEM2-ES run under the Representative Concentration Pathway 4.5 (RCP4.5) scenario. Wind speed data are similarly extracted but for the HadGEM2-ES run using the G4, as well as the G4cdnc and G4seasalt (Marine Cloud Brightening) GeoMIP scenarios. The solar and wind data are used to evaluate changes in solar photovoltaic (PV) and wind farm power generation in the Caribbean in future ‘SRM versus non-SRM worlds’. Solar irradiance resources and PV energy generation generally decrease under SRM compared to RCP4.5. The highest modelled mean change in PV generation across the region is, however, generally small, e.g., a maximum change of −1.37% for May-July for years corresponding to a 2.0 ∘C world. In contrast, wind power generation under SRM compared to RCP4.5 generally show large increases which are both seasonally and SRM technology dependent. For a 67m turbine, the highest regional wind generation change was +64.72 % for December-February under G4cdnc in a 2.0 ∘C world but −0.56%  under G4 in a 2.0 ∘C world for the same period. For a 100 m turbine, the highest change was an increase of 89.75% for August-September under G4cdnc in a 1.5 ∘C world and a decrease of −4.11% for December-January under G4 in a 2.0 ∘C world. Marine Cloud Brightening-based SRM scenarios (G4cdnc and G4SeaSalt) produce the most consistent spatial increases in wind power resources and generation compared to Stratospheric Aerosol Injection (G4). The findings of this study corroborate and present new findings about potential SRM induced changes on the VRE resources considered important for the Caribbean’s future development. It is therefore important that the region’s energy sector engage in the global discussions underway on the future use of SRM as a strategy for limiting future global warming.